The Impact of the Long-Distance Transport of a BEL1-Like Messenger RNA on Development - Lin, Tian (2013)
BEL1- and KNOTTED1-type proteins are transcription factors from the three-amino-loop-extension superclass that interact in a tandem complex to regulate the expression of target genes. In potato (Solanum tuberosum), StBEL5 and its Knox protein partner regulate tuberization by targeting genes that control growth. RNA movement assays demonstrated that StBEL5 transcripts move through the phloem to stolon tips, the site of tuber induction. StBEL5 messenger RNA originates in the leaf, and its movement to stolons is induced by a short-day photoperiod. Here, we report the movement of StBEL5 RNA to roots correlated with increased growth, changes in morphology, and accumulation of GA2-oxidase1, YUCCA1a, and ISOPENTENYL TRANSFERASE transcripts. Transcription of StBEL5 in leaves is induced by light but insensitive to photoperiod, whereas in stolon tips growing in the dark, promoter activity is enhanced by short days. The heterodimer of StBEL5 and POTH1, a KNOTTED1-type transcription factor, binds to a tandem TTGAC-TTGAC motif that is essential for regulating transcription. The discovery of an inverted tandem motif in the StBEL5 promoter with TTGAC motifs on opposite strands may explain the induction of StBEL5 promoter activity in stolon tips under short days. Using transgenic potato lines, deletion of one of the TTGAC motifs from the StBEL5 promoter results in the reduction of GUS activity in new tubers and roots. Gel-shift assays demonstrate BEL5/POTH1 binding specificity to the motifs present in the StBEL5 promoter and a double tandem motif present in the StGA2-oxidase1 promoter. These results suggest that, in addition to tuberization, the movement of StBEL5 messenger RNA regulates other aspects of vegetative development.